Provenance and Sediment Maturity as Controls on CO2 Mineral Sequestration Potential of the Gassum Formation in the Skagerrak - Olivarius, Mette; Sundal, Anja; Weibel, Rikke; Gregersen, Ulrik; Baig, Irfan; Thomsen, Tonny B.; Kristensen, Lars; Hellevang, Helge; Nielsen, Lars Henrik (Frontiers in Earth Science, 2019)
In order to meet the increasing demand to decarbonize the atmosphere, storage of CO2 in subsurface geological reservoirs is an effective measure. To maximize storage capacity, various types of saline aquifers should be considered including dynamic storage options with open or semi-open boundaries. In sloping aquifers, assessment of immobilization potential for CO2 through dissolution and mineralization along the flow path is a crucial part of risk evaluations. The Gassum Formation in Skagerrak is considered a nearshore CO2 storage option with layers shallowing northwards. In this study, petrographic data and provenance analysis provide the basis for estimating reactivity of the sandstones with respect to CO2 immobilization potential. These analyses are integrated with seismic interpretation, well-log analysis and sedimentological observations of sedimentary facies to estimate mineral distribution and corresponding reactivity in the proposed injection area. Here the Gassum Formation comprises south-prograding, shoreface-fluvial para-sequences, sourced from northern hinterlands. Pronounced differences in the mineralogical maturity in the studied area are identified and explained by the sediment transport distances and the type of sediment source. This is possible because the U-Pb ages of zircon grains in the sediments can be used to pinpoint the areas where they originate from in the Fennoscandian Shield, such as Telemarkia (gneissic) or Idefjorden (granitic) terranes. Of special importance are the most reactive mineral phases like albite and Fe-rich chlorite, of which the feldspar occurs in largest abundance and the grain-coating chlorite has largest surface area. Their distribution is partly controlled by provenance, so their abundance decreases basinwards with increasing sediment maturity. The abundance of fluvial sandstones presumably increases northwards in basal parts of para-sequences, while shoreface sandstones comprise the top part of sandy units. CO2 injected in the proposed area will migrate upwards within the reservoir and up-dip along the seal, towards more immature sediments (i.e. higher contents of albite and chlorite) and higher proportions of Telemarkian-derived sediment. Thus, the mineralization potential increases along the migration path, while kinetic reaction rates will decrease in shallower, lower temperature regions. Identifying these parameters is important to estimate the CO2 mineral sequestration potential and ensure safe storage of CO2.